Investigation of the spread of mercury in the land around the waste storage ponds in the Kulon Progo traditional gold mine - Ranno Marlany Rachman; Edward Ngii; Abdul Rahim Sya’ban (Journal of Degraded and Mining Lands Management, 2021)
This study was conducted to determine mercury contamination contained in soils in Kalirejo sub-district, Kulon Progo, Indonesia. This contamination occurred as a result of traditional gold mining activities that used the amalgamation method of mercury. Soil samples were collected from 6 sites; one site was located in an uncontaminated location, and 5 sites in contaminated soil were taken from 10 meters distance from the tailing ponds. Samples were collected from each site at 30, 60, and 90 cm depths. Mercury concentrations in each sample were measured according to the US EPA method, using Mercury analyzer type VM-3000. Mercury concentrations in uncontaminated area at 30, 60, 90 depths were 0.19 mg/kg, 0.02 mg/kg, and <0.0001 mg/kg respectively. These values did not exceed the quality standard according to Government Regulation No 101 The Year 2014 concerning Hazardous Waste Management of 0.3 mg/kg. Meanwhile, mercury concentrations around the tailing ponds were 0.30 to 22.51 mg/kg, which exceeded the quality standard.